1582 Pinehurst - Revels, Amber Dawn (East Carolina University, 2011)
Virginia "Ginny" Lovhaug lives her life by routine. Every day is exactly the same, varying little. She has a caring roommate, a bizarre best friend, and a loving boyfriend. However, someone in her life isn't who they seem to be. Notes and candy keep appearing on her bedroom table, and Ginny has no idea where they are coming from. Things soon come to a head, and Ginny has to make a decision. Will she choose her safety or her sanity?
Keywords: Film studies; Canadian literature; Stalking victims--Drama